2012
DOI: 10.4067/s0717-95022012000200039
|View full text |Cite
|
Sign up to set email alerts
|

Estudio Morfométrico del Seno Maxilar Mediante Tomografías Computadorizadas: Evaluación de la Reconstrucción Total de Piso Sinusal

Abstract: del seno maxilar mediante tomografías computadorizadas. Evaluación de la reconstrucción total de piso sinusal. Int. J. Morphol., 30(2):592-598, 2012. RESUMEN:La rehabilitación con implantes dentales en maxila posterior es compleja debido a la presencia del seno maxilar con sus diferentes variaciones anatómicas; el objetivo de este trabajo fue determinar el volumen óseo intrasinusal necesario para realizar la instalación de uno o mas implantes dentarios sin invadir la membrana sinusal. En 22 cráneos fueron eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Maxillary sinuses exhibit significant anatomic structures that are important to assess prior to implant placement. 1,2 However, the implant treatment could be modified by some findings in maxillary sinus such as pneumatization, hypoplasia, antral septa, and exostosis. 3 Ohba et al, 4 in a radiology forum, reported an incidence of maxillary sinus exostosis in 0.9% of the 2196 panoramic radiographs studied, being all of them unilateral cases, with predominance in the airway area and in female individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Maxillary sinuses exhibit significant anatomic structures that are important to assess prior to implant placement. 1,2 However, the implant treatment could be modified by some findings in maxillary sinus such as pneumatization, hypoplasia, antral septa, and exostosis. 3 Ohba et al, 4 in a radiology forum, reported an incidence of maxillary sinus exostosis in 0.9% of the 2196 panoramic radiographs studied, being all of them unilateral cases, with predominance in the airway area and in female individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Estas relaciones anatómicas son relevantes al momento de la planificación de tratamientos mediante implantes dentales u otras cirugías que involucren el abordaje de la zona. Chiapasco & Zaniboni (2009);de Moraes et al (2012) y Mendoza et al (2013) describen relaciones del reborde y los dientes en la zona posterior y piso del seno maxilar, pero no encontramos otros reportes utilizando TCCB relacionando la zona anterior maxilar alrededor de los caninos y premolares.…”
Section: Discussionunclassified
“…It is quite often the first-choice test to evaluate the maxillary sinuses, as it enables one to evaluate the size, pneumatization and findings inside them. 7,28 Despite its importance as a diagnostic aid, radiographic examination must not be indistinctly performed for all individuals, only when the patient's history or their signs and symptoms suggest this need and when the information it offers is of great use. 9,13,14 However, a three-dimensional image may be necessary, such as CBCT obtained in axial sections (the interval between the cuts is variable), in order to increase the accuracy of the images, enabling better diagnosis and planning.…”
Section: Introductionmentioning
confidence: 99%